Evidence of habitual behavior from non-alimentary dental wear on deciduous teeth from the Middle and Upper Paleolithic Cantabrian region, Northern Spain. Issue 158 (September 2021) - Estalrrich, Almudena; Marín-Arroyo, Ana B.
Abstract: The use of 'teeth as tools' (non-masticatory or cultural-related dental wear) has largely been employed as a proxy for studying of past human behavior, mainly in permanent dentition from adult individuals. Here we present the analysis of the non-masticatory dental wear modifications on the deciduous dentition assigned to eight Neanderthal and anatomically modern human subadult individuals from Mousterian to Magdalenian technocultural contexts in the Cantabrian region (Northern Spain). Although preliminary, we tentatively suggest that these eight subadults present activity-related dental wear, including cultural striations, chipped enamel, toothpick grooves, and subvertical grooves. We also found evidence of habitual dental hygienic practices in the form of toothpicking on a deciduous premolar. Orientation of the cultural striations indicates similar handedness development as in modern children. Taken together, these dental wear patterns support the participation of young individuals in group activities, making them potential contributors to group welfare. This study potentially adds new evidence to the importance of the use of the mouth in paramasticatory activities or as a third hand throughout the Pleistocene, which can be confirmed with a more specific reference sample.